PERAN SEKTOR INDUSTRI PENGOLAHAN DALAM PEREKONOMIAN EMPAT PROVINSI DI PULAU JAWA - Akhmad Solikin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Manufacturing sector is substantial for economic development in terms of economic growth, value added, export, and employment. This article investigates and compares manufacturing sectors’ roles on economies in four provinces in Java Island, Indonesia, i.e. the Province of Banten, Jawa Barat, Jawa Tengah and Jawa Timur. This article used secondary data in terms of Input Output Table in general and backward linkage effect ratio and forward linkage effect ratio in particular. By doing so, the article discusses leading sectors in manufacturing subsectors. The Input Output Tables were published by BPS in 2021 which represents 2016 data. The results show that five manufacturing industries play significant roles as leading sectors, i.e. food and beverages, textile and garments, paper and printing, chemical and pharmacy, and rubber and plastic. In contrast, tobacco processing, coal and oil refinery, and base metal are three manufacturing subsector which are not included in key sectors in majority of provinces. In general, more manufacturing sectors have stronger backward linkage effects ratio rather than forward linkage effects ratio. The provincial governments could use information about leading sectors in development planning, such as Medium-Term Development Planning (RPJMD) in quest to achieve more sustainable developments.